Comparison of endorectal coil and nonendorectal coil T2W and diffusion‐weighted MRI at 3 Tesla for localizing prostate cancer: Correlation with whole‐mount histopathology. Issue 6 (15th November 2013) - Turkbey, Baris; Merino, Maria J.; Gallardo, Elma Carvajal; Shah, Vijay; Aras, Omer; Bernardo, Marcelino; Mena, Esther; Daar, Dagane; Rastinehad, Ardeshir R.; Linehan, W. Marston; Wood, Bradford J.; Pinto, Peter A.; et al.
Abstract : Purpose: To compare utility of T2‐weighted (T2W) MRI and diffusion‐weighted MRI (DWI‐MRI) obtained with and without an endorectal coil at 3 Tesla (T) for localizing prostate cancer. Materials and Methods: This Institutional Review Board‐approved study included 20 patients (median prostate‐specific antigen, 8.4 ng/mL). Patients underwent consecutive prostate MRIs at 3T, first with a surface coil alone, then with combination of surface, endorectal coils (dual coil) followed by robotic assisted radical prostatectomy. Lesions were mapped at time of acquisition on dual‐coil T2W, DWI‐MRI. To avoid bias, 6 months later nonendorectal coil T2W, DWI‐MRI were mapped. Both MRI evaluations were performed by two readers blinded to pathology with differences resolved by consensus. A lesion‐based correlation with whole‐mount histopathology was performed. Results: At histopathology 51 cancer foci were present ranging in size from 2 to 60 mm. The sensitivity of the endorectal dual‐coil, nonendorectal coil MRIs were 0.76, 0.45, respectively. PPVs for endorectal dual‐coil, nonendorectal coil MRI were 0.80, 0.64, respectively. Mean size of detected lesions with nonendorectal coil MRI were larger than those detected by dual‐coil MRI (22 mm versus 17.4 mm). Conclusion: Dual‐coil prostate MRI detected more cancer foci than nonendorectal coil MRI. While nonendorectal coil MRI is an attractive alternative, physicians performing prostate MRI should be aware of its limitations.J. Magn. Reson. Imaging 2014;39:1443–1448 . ©2013 Wiley Periodicals, Inc.